Sistem Otomatisasi Pembersihan Kotoran dan Pengaturan Suhu Kandang Kelinci Berbasis Arduino Mega2560 - Eko Didik Widianto; Mahfudhotul Khasanah; Agung Budi Prasetijo; Risma Septiana (Universitas Syiah Kuala, 2017)
The environmental factor of the cage affects the rabbit breeding. The more rabbits, the more efficient cage cleaning needs to be done. This research resulted in an automation system prototype of dirt cleaning and temperature control of rabbit cage using Arduino Mega 2560 board. The system was capable of monitoring and controlling the cage temperature of 26-36 ° C using DHT11 temperature sensor, heating, and cooling actuators. The system performed the cage manure cleaning by controlling the motion of the servo motor after processing the input from the load cell weight sensor with the capability of 5 kg. Dirt cleaning is done if the weight of the dirt is above 1000 gram. This research also applied linearization to produce temperature and weight conversion equations which yielded more accurate reading values. The temperature readings had an accuracy of ± 1 ° C, while the load cell weight reading had an accuracy of 0.05% or 2 grams.